Quality of Life Analysis with WHOQOL-BREF in Disaster Preparedness for Flood-Prone Areas in Makassar City, Indonesia - Latief, Rachmat; Budu, .; Tumpu, Miswar; Hatta, Mukhsan Putra; Aprianti, Evi (Engineering, Technology & Applied Science Research, 2025)
Floods are recurring disasters in urban areas, particularly in flood-prone regions, such as Makassar City, Indonesia. The preparation of residents for such events is crucial for reducing risks and enhancing resilience. This study aims to analyze the relationship between Quality of Life (QoL), as measured by the World Health Organization Quality of Life-BREF (WHOQOL-BREF), and disaster preparedness in flood-prone areas of Makassar City. A combination of conventional statistical methods and Structural Equation Modeling- Partial Least Squares (SEM-PLS) was used to analyze the data collected from 409 respondents across four sub-districts: Biringkanaya, Tamalanrea, Panakkukang, and Manggala. The findings indicate that a higher QoL correlates with improved disaster preparedness, suggesting that efforts to enhance residents' well-being can positively influence their readiness for floods. Based on these results, this study proposes integrating QoL factors into disaster preparedness programs to increase community resilience.